Odpowiedź :
Szczegółowe wyjaśnienie:
36.
Korzystamy ze wzoru: [tex]a^{log_{a}c } =c[/tex]
a) [tex]3^{log_{3} 5} =5[/tex]
b) [tex]16^{log_{2}\frac{1}{3} } =2^{4} ^{log_{2}\frac{1}{3} }=[/tex] ← [tex]4log_{2} \frac{1}{3} =log_{2} (\frac{1}{3} )^{4} =log_{2} \frac{1}{81}[/tex]
[tex]=2^{log_{2}\frac{1}{81} } =\frac{1}{81}[/tex]
[tex]\frac{3^{log_{3}5 } }{16^{4log_{2}\frac{1}{3} } }=\frac{5}{\frac{1}{81} } =5:\frac{1}{81}=5*81=405[/tex]
37.
Korzystamy z definicji logarytmu:
[tex]log_{a} c=b[/tex] ⇔ [tex]a^{b} =c[/tex] [tex]a > 0[/tex] i [tex]a\neq 1[/tex] , [tex]c > 0[/tex]
a)
[tex]log_{a}\sqrt{3} =\frac{1}{2} \\[/tex]
[tex]a^{\frac{1}{2} } =\sqrt{3}[/tex]
[tex]a^{\frac{1}{2} } =3^{\frac{1}{2} }[/tex]
[tex]a=3[/tex]
b)
[tex]log_{b} \frac{1}{4} =-3\\[/tex]
[tex]b^{-3} =\frac{1}{4}[/tex]
[tex]b^{3} =\frac{4}{1}[/tex]
[tex]b^{3} =4[/tex]
[tex]b=\sqrt[3]{4}[/tex]
c)
[tex]log_{c}0,2 =-0,5[/tex]
[tex]c^{-0,5} =0,2[/tex] ← [tex]0,2=\frac{2}{10}=\frac{1}{5}[/tex]
[tex]c^{-\frac{1}{2} } =\frac{1}{5}[/tex]
[tex]c^{\frac{1}{2} } =5[/tex]
[tex]\sqrt{c} =5[/tex] [tex]/^{2}[/tex]
[tex]c=25[/tex]
∛4 < 3 < 25
b < a < c